2000
DOI: 10.1021/es9913683
|View full text |Cite
|
Sign up to set email alerts
|

Natural Background Levels of Trifluoroacetate in Rain and Snow

Abstract: It has been shown that some of the fluorinated ethane derivatives being introduced as CFC-replacements can be transformed to TFA (trifluoroacetate) in the atmosphere. Moreover, TFA is extremely stable in the environment, and this has raised questions regarding how widespread TFA is in the environment. We found that TFA is ubiquitous in precipitation: samples of rain from Ireland and Poland and snow from Canada, Sweden, New Zealand, and East Antarctica contained 1-1100 ng/L, and, studying a firn core drilled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…TFA levels in rainwater from Guangzhou were about one order of magnitude higher than those in Mace Head, Ireland in 1996 (Von Sydow et al, 2000), and were much higher than those reported in Baikal, Siberia ) in 1996 (Berg et al, 2000), but in similar range with those reported in Tübingen (Frank et al, 1995), Beijing (Zhang et al, 2005), California and Nevada (Wujcik et al, 1998). The average level in this study was even lower than that in Central Valley, California in 1996 (Wujcik et al, 1998).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…TFA levels in rainwater from Guangzhou were about one order of magnitude higher than those in Mace Head, Ireland in 1996 (Von Sydow et al, 2000), and were much higher than those reported in Baikal, Siberia ) in 1996 (Berg et al, 2000), but in similar range with those reported in Tübingen (Frank et al, 1995), Beijing (Zhang et al, 2005), California and Nevada (Wujcik et al, 1998). The average level in this study was even lower than that in Central Valley, California in 1996 (Wujcik et al, 1998).…”
Section: Resultssupporting
confidence: 58%
“…TFA has become a ubiquitous contaminant and has been detected in a variety of environmental media, such as air (Frank et al, 1996), precipitation (Jordan and Frank, 1999;Scott et al, 2006;Zehavi and Seiber, 1996), fog (Römpp et al, 2001), surface waters (Cahill and Seiber, 2000;Scott et al, 2000Scott et al, , 2002Zhang et al, 2005), soils and pine needles Scott et al, 2005b), oceans (Frank et al, 2002;Scott et al, 2005a) and even in the snow of the Arctic and Antarctica (Von Sydow et al, 2000). TFA is extremely stable in the ambient and highly resistant to chemical and biological degradation under normal environmental condition (Emptage et al, 1997;Boutonnet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier methods of analysis of TFA were based on GC with mass spectrometry or GC with electron capture detection [9,10,20,21,24,25]. The LOQ of the GC methods was several ng L −1 .…”
Section: Optimization Of Ms/ms Parameters For Short-chain Pfasmentioning
confidence: 99%
“…Whereas short-chain PFCAs such as TFA are phytotoxic, long-chain PFCAs are considered to be carcinogenic and bioaccumulative. Earlier studies have measured TFA in water samples by gas chromatography (GC) techniques after chemical derivatization [20][21][22]. Because derivatization introduces additional, time-consuming analytical steps in the analysis of TFA, a method to determine TFA using HPLC-MS/MS (which does not require derivatization) will enhance the throughput and robustness of the analysis.…”
Section: Introductionmentioning
confidence: 99%